A cross-sectional study to assess the knowledge, attitudes, and practices of cervical cancer screening/pap smear among health care professionals in a tertiary care hospital in North India - Aggarwal, Richa; Mathe, Priyanka; Sharma, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is one of the most easily preventable and curable cancers among females. It imposes a high burden on developing countries, and with the use of screening methods, higher detection rates can be assured. Aims and objectives were to evaluate the knowledge, attitudes, and practices (KAPs) among health care professionals including doctors, nurses, and laboratory technicians regarding a very simple test for cervical cancer screening (i.e., Pap smear) Methods: This was a descriptive cross-sectional study that was conducted on 200 female health care workers in University College of Medical Sciences and Guru Teg Bahadur Hospital, Delhi from August 2018 to July 2022. A pretested, self-administered questionnaire was used on health care professionals working in various departments. This questionnaire collected information on sociodemographic data, knowledge regarding cervical cancer screening, Pap smear, and HPV vaccination, and attitudes of participants toward a Pap smear and HPV vaccination. Results: A total of 200 health care workers participated and knowledge among doctors and paramedical staff was compared but only 24.05% of the doctors and 26.44% of the paramedical staff had ever undergone a Pap smear screening, which was statistically insignificant (p=0.7). Awareness about the cervical cancer prevention vaccine was found more among doctors (n=78, 98.7%) than paramedical staff (n=77, 63.63%), and this was found to be statistically significant (p=0.001) Also, data among participants from a gynecology department (GD) versus other departments was compared, and awareness regarding HPV vaccine was much higher in the other-than-gynecology department (OTGD) group (84.29%) versus the GD group (59.54%), and this was statistically significant (p<0.001). Conclusions: Health care workers play an essential role in the community to spread awareness, but there is a need for a change in attitude about the disease and its screening. We can utilize this knowledge in filling the critical gaps in the community regarding awareness, screening, and prevention of the disease.